Stereochemical modulation of emission behaviour in E/Z isomers of diphenyldipyrroethene from aggregation induced emission to crystallization induced emission1. Issue 29 (7th August 2015) - Garg, K.; Ganapathi, E.; Rajakannu, P.; Ravikanth, M.
<x xml:space="preserve">Abstract</x> We have successfully separated and characterized E- and Z-isomers of diphenyldipyrroethene molecules and studies show that the E-isomer behaves as AIEgen, whereas the Z-isomer behaves as CIEgen.